PENGARUH MOTIVASI, LINKUNGAN KERJA DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN (PT. Arafura Marine Culture-Kepulauan Aru) - Ade Saputra Sastro; Hadi Sunaryo; M. Khoirul Abs (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT  This study aims to determine the effect of motivation, work environment and employee engagement on employee performance. The research sample in this study amounted to 68 people who are employees of PT. Arafura Marine Culture.The method used is descriptive data analysis using validity, reliability, normality, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, hypothesis testing f, and hypothesis t test. The results of this study indicate that the variables of motivation, work environment, and employee engagement, while partially each of the motivation and work environment variables both affect employee performance but employee engagement does not affect the performance of employees of PT. Arafura Marine Culture. Keywords: motivation, work environment, employee engagement, employee performance